The Spiral of Anxiety in the 2024 Presidential Election Discourse on X - Nurul Islam; Alexander Beny Pramudyanto; Muliadi Muliadi; Nuryadin Nuryadin (Jurnal Riset Komunikasi, 2026)
This study explores the emergence of a spiral of anxiety among social media users on X (formerly Twitter) during the Indonesian 2024 presidential election discourse. Drawing upon the spiral of silence theory, this research investigates how users respond emotionally when their political opinions diverge from the perceived majority, particularly under conditions of high polarization. Using a quantitative sentiment analysis approach, the study analyses 1,060 tweets collected through six election-related hashtags between November 13, 2023, and February 14, 2024. The data were classified using the Naïve Bayes Classifier (NBC) method and validated on Google Collab. The findings reveal that while polarized users often express strong sentiments, a significant proportion of users exhibit neutral tones, interpreted as a strategic silence or emotional withdrawal due to fear of backlash. This silence does not stem from indifference, but from socio-political anxiety, indicating a transformation from a spiral of silence to a spiral of anxiety. As a result, the quality of discourse declines, shifting from fact-based debate to emotionally charged opinion exchanges. This phenomenon contributes to unproductive political engagement and increased social fragmentation. The study offers theoretical and empirical insights into how digital platforms shape political communication in highly polarized societies.